Introduction to Azure - Kennedy, Norm; Safari eBooks ([Place of publication not identified] : CompuWorks, 2016)
"This course will introduce students to the Cloud, types of Cloud services, Azure services, and Azure PowerShell. The content provides the pre-requisite knowledge required by all individuals who will be learning Microsoft Azure. Students who are administrators, developers, or database administrators will benefit from learning the fundamentals covered in this course and will be better prepared to take additional Microsoft Azure courses that are generally more advanced. "--Resource description page.
Title from resource description page (Safari, viewed August 31, 2016).
Presenter, Norm Kennedy.
Keywords: Windows Azure; Cloud computing; Application software -- Development; Electronic books